Pemanfaatan Aplikasi Google Maps Sebagai Upaya Digitalisasi UMKM Sangkar Burung di Dukuh Dayakan Desa Wagir Lor Kab. Ponorogo - Ilham Syah; Khoirul Fathoni (Social Science Academic, 2025)
This community service program aims to support the digitalization of Micro, Small, and Medium Enterprises (MSMEs) through the utilization of Google Maps as a business promotion medium. The activity was carried out at the birdcage MSME “Setia Sangkar,” located in Dukuh Dayakan, Wagir Lor Village, Ngebel Subdistrict, Ponorogo Regency, on July 31–August 1, 2025. The method applied was *Participatory Action Research (PAR)*, which included site surveys, observations, interviews, and hands-on training on creating Gmail accounts, adding business locations, and completing business profiles on Google Maps. The results showed an increase in digital literacy and enthusiasm among MSME owners in utilizing technology to expand their market reach. MSME products became more accessible to consumers through geotagging features and complete business information. This training also highlights that simple digital literacy efforts can have a significant impact on the competitiveness of MSMEs in the digital era. Further assistance is required to ensure sustainable and optimal use of Google Maps.